Implementasi Marketday Dalam Membangun Kreatifitas Siswa Di MA Al-Hamidiyah - George Khatami Albusthomi; Imam Hasani; Hamam Thoriq Majid; Imran Revanza (Asosiasi Riset Ilmu Manajemen dan Bisnis Indonesia, 2024)
On certain days, schools participate in Market Day by asking children to make real-life sales and purchases. Students participate in all stages of the supply chain from manufacturing to distribution to consumption during Market day, an example of an integrated entrepreneurship education program. Students can also appreciate their abilities during Market Day. The aim of this research is to help Madrasah Aliyah Al-Hamidiyah Depok students become more imaginative. A qualitative research approach was used in this research. Observation and interviews are the methods used to collect data. These findings indicate that students' originality develops after they participate in Market day at school.